Pride and Prejudice: Using Ethnic-Sounding Names and Inter-Ethnic Marriages to Identify Labour Market Discrimination - Rubinstein, Y.; Brenner, D. (Review of Economic Studies, 2014)
Do labour markets discriminate against workers with particular ethnic-sounding names? We use non-random sorting into inter-ethnic marriage and salient differences between Sephardic and Ashkenazi surnames to evaluate the causal impact of Sephardic affiliation on wages. Using the 1995 Israeli Census, we estimate the effect of a Sephardic sounding surname on wages. We first compare the wages of Israeli Jewish males born to Sephardic fathers and Ashkenazi mothers (SA), who are more likely to carry a Sephardic surname, with the wages of Israeli Jewish males born to Ashkenazi fathers and Sephardic mothers (AS). We find that Israeli labour markets discriminate based on perceived ethnicity: SA workers earn significantly less than their AS counterparts. We then exploit the custom of women to adopt their husbands' surnames to disentangle actual ethnicity from the ethnicity perceived by the market. Consistent with ethnic discrimination based on surnames, we find that it is father-in-law's ethnicity–rather than father's ethnicity–that shapes female wage rates. Finally, we find that labour markets discriminate based on surname only when those names provide additional information about ethnicity. When ethnicity can be discerned from skin tone, surnames do not provide additional explanatory power with respect to wages. Copyright 2014, Oxford University Press.